Songthaew Service Patterns in Areas Surrounding Rail Transit Stations in Bangkok and Its Vicinity - Pandhawuttiyanon, Bandhita; Sanit, Peamsook (King Prajadhipok’s Institute Journal, 2025)
Songthaew is a form of paratransit service that functions as a feeder mode. It plays a significant role in overcoming transportation limitations by providing small vehicles that can access narrow alleys and facilitate the transfer of passengers to the mass transit system. In addition, Songthaew is recognized as an informal transportation option, characterized by greater flexibility and adaptability to varying conditions and changes compared to fixed-route mass transit systems. This study aims to survey and analyze Songthaew service patterns and adaptations in the areas surrounding rail stations in Bangkok and its vicinity. The target population consists of Songthaew service providers, including drivers, managers, and entrepreneurs, who operate within 500 meters of the rail transit stations. These stations include the BTS Light Green Line, Dark Green Line, MRT Blue Line, Purple Line, Yellow Line, SRT Red Line, and the Airport Rail Link. The sampling method employed is purposive sampling.One sample represents a single Songthaew line. The results of this study indicate that Songthaew service patterns vary depending on land use. Songthaew providers operating around low-density residential area stations tend to have longer distance routes with lower frequencies compared to those serving urban high-density and commercial area stations. Furthermore, Songthaew services have been adapted to support the rail transit system in high-density and commercial areas, primarily by offering longer distance routes. However, the adjustment of service patterns is not significantly related to land use; rather, it is influenced by the policies of the service providers, which aim to address the issue of declining passenger numbers. For this reason, a policy to support Songthaew as a feeder mode for the rail transit system is essential for the sustainable development of the mass transit system.